The effect of L-dopa in Parkinson's disease as revealed by neurophysiological studies of motor and sensory functions. (1st February 2017) - Suppa, Antonio; Bologna, Matteo; Conte, Antonella; Berardelli, Alfredo; Fabbrini, Giovanni
ABSTRACT: Introduction: This review will first discuss evidence of motor and sensory abnormalities as yielded by neurophysiological techniques in patients with PD. It will then go on to describe the effects of L-dopa replacement on motor and sensory abnormalities in PD as assessed by neurophysiological studies. Areas covered: We analyzed papers in English using Pubmed with the following keywords: L-dopa, dopamine, bradykinesia, basal ganglia, kinematic analysis, TMS, motor cortex plasticity, motor cortex excitability, somatosensory discrimination threshold, pain Expert commentary: L-dopa improves the amplitude and speed of upper limb voluntary movements, but it does not restore abnormalities in the sequence effect or voluntary facial movements. L-dopa only partially normalizes changes in motor cortex excitability and plasticity and has also contrasting effects on the sensory system and on sensory-motor integration. The neurophysiological studies reviewed here show that PD is more than a hypo-dopaminergic disease, and non-dopaminergic mechanisms should also be considered.